Flotation—A New Method to Circumvent PCR Inhibitors in the Diagnosis of Lawsonia intracellularis - Jacobson, Magdalena (Hindawi Publishing Corporation, 2009)

(untitled)
The obligate intracellular bacterium Lawsonia intracellularis causes enteritis and poor growth in weaned pigs. Cultivation is difficult and diagnosis ante mortem is mainly based on techniques such as polymerase chain reaction. However, false negative results caused by the presence of PCR-inhibitory factors constitute a problem. This study aimed to develop and evaluate a new technique, flotation, to separate L. intracellularis from inhibitors in faeces prior to PCR. The technique was evaluated by comparison to two previously evaluated and commonly used methods, preparation by boiling lysate combined with nested PCR and preparation by a commercial kit combined with conventional PCR. Continuous density centrifugation of faecal samples containing L. intracellularis suggested the buoyant density of the microbe to be between 1.064 and 1.077 g/mL. Several flotation setups were tested to achieve optimal separation of the microbe from inhibitors and faecal particles. The finally selected setup floated whole L. intracellularis from the application site at the bottom to the upper part of the gradient while inhibitory components mainly remained in the bottom. PCR was performed directly on material recovered from the upper interphase. The method was evaluated on 116 clinical samples. As compared to sample preparation by boiling combined with nested PCR, fewer samples were inhibited but also fewer positives were identified. In comparison to preparation by a commercial kit combined with conventional PCR, presently used for routine diagnosis, similar results were obtained. However, the new method was comparably faster to perform. The new method, based on flotation of Lawsonia intracellularis combined with conventional PCR, was well suited for routine diagnosis.